Ion release of chitosan and nanodiamond modified glass ionomer restorative cements - Mulder R; Anderson-Small C (Dove Medical Press, 2019)
Riaan Mulder1, Charney Anderson-Small2 1Paediatric Dentistry, The University of the Western Cape, Cape Town, South Africa; 2Central Analytical Facilities, Stellenbosch University, Cape Town, South AfricaCorrespondence: Riaan MulderPaediatric Dentistry, The University of the Western Cape, Office 2129 C-floor, UWC Dental Faculty, Fransie van Zijl Drive, Cape Town 7505, South AfricaTel +27 21 937 3107Email rmulder@uwc.ac.zaPurpose: Ion release from glass ionomer restorative cements (GICs) plays an important role in GICs. The ion release from chitosan and nanodiamond-modified glass ionomers was assessed.Materials and methods: Three GICs (Fuji IX, Ketac Universal and Riva Self Cure) were modified in the powder phase per weight by adding 5% or 10% of a commercially available chitosan powder (CH) or nanodiamond (ND) powder to the GICs. The specimens with dimensions 4 mm diameter and 6 mm height manufactured from the 15 GIC formulations were allowed to set for 1 hr and subsequently placed in neutral de-ionised water. The released ions were assessed using inductively coupled plasma-mass spectrometer (ICP-MS) to determine the elemental release. Additionally, three different disc-shaped specimens (3 mm in diameter and 1 mm thick) were constructed from each material for scanning electron microscopy (SEM) and energy dispersive X-ray spectrometry (SEM-EDS) microanalysis to establish an ion weight percentage.Results: There were no significant differences in the ion release between the control materials for aluminium, silicon and strontium. The ion release from CH and most ND-modified GICs were significantly (p<0.00001) increased compared to the control materials. CH modifications significantly increased the ion release of aluminium, sodium, silicon and strontium for all three control materials (with the exception of the strontium release from Ketac Universal that was modified with 5% chitosan).Conclusion: Ion release can be advantageous to tooth structure due to the interaction of chitosan with the GIC chemistry and moisture during maturation. Ion release up to five times greater than the control was noted for some ions.Keywords: glass ionomer cement, chitosan, nanodiamond, ICP-MS, aluminium, strontium